COMPARISON OF HEALTH-RELATED PHYSICAL FITNESS AND ITS ASSOCIATION WITH THE LENGTH OF SERVICE BETWEEN SPECIAL OPERATIONS AND TRAFFIC MILITARY POLICE OFFICERS - Jarbas Rállison Domingos-Gomes; Leandro Sávio Oliota-Ribeiro; Josivan de Sousa Silva; Amauri Coutinho de Melo; Severino Leão de Albuquerque Neto; Maria do Socorro Cirilo-Sousa; Rodrigo Ramalho Aniceto (Journal of Physical Education)
ABSTRACT This study compared health-related physical fitness (HRPF) between military policemen (MP) from the Special Police Operations Battalion (BOPE) and from the Traffic Police Battalion (BPTRAN) and related the military time of service with the variables of HRPF. The sample was composed of 47 MPs from the city of Patos, state of Paraíba, Brazil, aged between 26 and 49 years old and who had served for 3 to 30 years (BOPE, n=25; BPTRAN, n=22). A battery of tests was performed: anthropometric assessment, Wells sit-and-reach test, 1 min sit-up test, elbow flexion and 20 m shuttle run test. The BOPE and the BPTRAN did not differ regarding HRPF, except for flexibility, which was higher for the BOPE (p=0.026). In addition, the findings showed that the time of service negatively affected the morphological, neuromuscular and cardiorespiratory fitness of the MP officers.